Estimation of the Date Production Function in Libya during the Period (1995-2020) - Azrrigany, Mahmood O.; Doub, Hajer A. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This study aimed to estimate the production function of dates in Libya using the Cobb-Douglas production function with constant elasticity, based on time series data for the period (1995-2020) after testing for stationary. The quantitative ARDL methodology was employed, along with the Indicator Saturation method to explore outliers and structural changes by incorporating dummy variables. The analysis was conducted using the statistical software Eviews (versions 10-13), GRETL, and Excel. The findings indicate that the production function of dates during the study period is capital-intensive. Specifically, a 10% increase in capital leads to a 10.7% increase in date production. Additionally, the function shows a positive relationship with labor, where a 10% increase in labor results in a 1.2% increase in date production. Comparing the elasticity of labor and capital, the results demonstrate that the date production function is capital-intensive.
Keywords: Cobb-Douglas Function; Production Elasticity; Returns to Scale; Date Production; Indicator Saturation